A comparative design of 5G communication codes - Anand Kumar, V.; Nandalal, V. (International journal of communication systems, 2024)
Summary Channel coding is the most significant part of every communication system. Future wireless systems will require extraordinary performance codes employing a low‐complication encoding process and decoding to accommodate scenarios ranging from effective throughput with low code rates for extended messages to high dependability for brief information messages with low code rates. The existence of digital transmission techniques that can communicate error‐free over a noisy channel is established by Shannon's channel theorem. Channel coding, however, increases communication dependability at the cost of higher computational costs and structured redundancy. The primary goals of the fifth‐generation cellular network (5G) are enhanced dependability, reduced redundancy, and decreased latency. Two promising communication systems for achieving this goal are LDPC codes and polar codes. The 3GPP, which established the 5G communication system, is reviewed in this paper, along with the encoding/decoding procedure and communication dependability. The encoding/decoding process will be evaluated using the three most studied communication channels: the Binary Erasure Channel (BEC), AWGN (Additive White Gaussian Noise), and the BSC (Binary Symmetric Channel). In the proposed work, the comparison of LDPC code and polar coder are done based on 5G standard. Performance of coding technique is compared with short length code (64,128), with a code rate of ½. The throughput of both coding techniques is plotted. LDPC code's speed improves with block length; longer blocks complicate coding and decoding. The Bit Error Rate (BER) and FER of binary LDPC‐polar codes to demonstrate the advantages of the suggested LDPC‐polar codes. Binary LDPC (32, 28) and binary polar (256, 96) codes form the LDPCpolar scheme. The SC method is used to decode the inner polar code. Inner polar codes are decoded using SC, and the bit probabilities produced by the polar decoder are utilized to compute the symbol probabilities of LDPC codes roughly.